Islamic home financing under Al-Ijarah Thumma Al-Bai: the influential factor / Ahmad Lokman Alias - Alias, Ahmad Lokman (2013)
The aim of this paper is to investigate influential factor toward Islamic home financing under Al-Ijarah Thumma Al-Bai (AITAB) in Malaysia. More specifically to examine the reason of consumers’ for selecting AITAB home financing rather than conventional home financing. AITAB or known as lease followed with sale is perhaps most popular product used by Malaysia financial institution in providing facilities to their customer. AITAB is a contract on the transferring the right of a goods or services through the payment of a wages on the rent, without being followed by the transfer of the ownership (milkiyah) on the goods itself. The feature of the AITAB has been controversial when there are high level of satisfaction anticipated among the present and potential AITAB customer including Muslim and non-Muslim. There is great potential for AITAB to be marketed in the future to different segments of customers ranging from people who are concerned about the validity of that financing facility, and those who are looking for convenience and less complicated transactions